OBJECT CONTROL OF GOLD INSTALLMENT SALE AND PURCHASE TRANSACTIONS IN BUKALAPAK IN THE PERSPECTIVE OF LIL AMRI BISY SYIRA’ MURABAHAH CONTRACT - Jabbar Sabil; Wirda Munira (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2022)
Bukalapak presents gold buying and selling transactions online through the Buka Emas feature. The author is interested in studying the control of the object of sale and purchase from the perspective of a murabahah lil amr lisy syira’ cotntract. The formulation of the problem: 1) how is the control over the object in buying and selling gold in installments at Bukalapak? 2) what is the perspective of the murabahah lil amr bisy syira’ contract on the non-cash buying and selling of gold at Bukalapak? The research method used is a case study, data obtained through field research. It was found that the object of sale and purchase was not given to users who bought gold, on the grounds of avoiding potential losses between the two parties. However, users can monitor the details of the installments submitted from the installment info page. This has the potential to cause fraud and default, so it is recommended that related parties and Bukalapak can guarantee that the item is available and can be owned.